Physicochemical properties and operational stability of Taguchi design-optimized Candida rugosa lipase supported on biogenic silica/magnetite/graphene oxide for ethyl valerate synthesis - Jacob, A.G. (Elsevier B.V., 2022)
Biobased ternary nanocomposites can stabilize enzymes for greater stability, catalytic activity and easy recovery. This study aimed to optimize biogenic silica/magnetite/graphene oxide nanocomposite supported Candida rugosa lipase (CRL/SiO2/Fe3O4/GO) for ethyl valerate (EV) synthesis and characterize the biocatalystsâ physicochemical properties and operational stability. CRL conjugated-oil palm leaves-derived biogenic SiO2/Fe3O4/GO nanocomposite showed a maximum immobilized protein of 44.13 Â± 2.1 mg/g with a specific activity (534.87 Â± 9.5 U/mg), than free CRL (â¥700 U/mg). GL-A-SiO2/Fe3O4/GO exhibited the highest surface area (260.87 m2/g) alongside superior thermal stability in TGA/DTG. XRD revealed an amorphous SiO2 (crystallinity = 26.7), while Fe3O4 existed as cubic spinel crystal (crystallinity = 90.2). Taguchi Design-optimization found that CRL/SiO2/Fe3O4/GO best catalyzed the EV synthesis (90.4 in 3 h) at 40 â using 3 mg/mL of biocatalyst, valeric acid/ethanol molar ratio of 1:2, in 10 (m/v) molecular sieves with stirring in heptane at 200 rpm. EV production was confirmed by FTIR- (C=O: 1738 cmâ1 and CâOâC: 1174 cmâ1) and GCâMS (M+ m/z = 130, C7H14O2). CRL/SiO2/Fe3O4/GO's reusability for 11 successive esterification cycles demonstrated the SiO2/Fe3O4/GO's exceptional hyperactivation and stabilization properties on immobilized CRL. These findings conveyed the SiO2/Fe3O4/GO's efficacy to alter CRL's physicochemical properties and operational stability for catalyzing higher yields EV. Â© 2021 The Society of Powder Technology Japan